2018
DOI: 10.1152/ajpheart.00347.2018
|View full text |Cite
|
Sign up to set email alerts
|

Tefillin use induces remote ischemic preconditioning pathways in healthy men

Abstract: Acute tefillin use improves vascular function while chronic tefillin use is associated with an anti-inflammatory RIPC-like phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…This clinical study was designed to use a HRV monitoring device on healthy human volunteers in order to determine if there was a correlation between our previous studies using tefillin [ 20 , 23 ] and changes in HRV parameters. Though we attempted to eliminate many stimuli that can affect HRV (exclusion criteria listed in Study Design), there are additional factors found in the literature that were not accounted for in this small preliminary study [ 33 , 34 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This clinical study was designed to use a HRV monitoring device on healthy human volunteers in order to determine if there was a correlation between our previous studies using tefillin [ 20 , 23 ] and changes in HRV parameters. Though we attempted to eliminate many stimuli that can affect HRV (exclusion criteria listed in Study Design), there are additional factors found in the literature that were not accounted for in this small preliminary study [ 33 , 34 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory and others have investigated the RIPC effect in different animal [ 20 , 21 ] and human conditions [ 19 , 22 ] and have found that ischemia itself is not necessary to induce RIPC as the effect appears to be mediated by pain sensation and at least partially through transient potential receptor vanilloid (TRPV) channel stimulation [ 20 , 21 ]. Further, we have documented that the effect can be elicited by non-obstructive banding (NOB) of an extremity in healthy male individuals through the use of tefillin, which is a box with sacred texts attached to a leather strap that is traditionally bound to the non-dominant arm of Jewish adults during morning prayers [ 23 ]. The strap is usually worn for approximately 30 minutes in a manner that is tight enough to result in indentations in a helical manner on the skin of the arm and forearm but not tight enough to completely obstruct blood flow to the extremity.…”
Section: Introductionmentioning
confidence: 99%
“…2 Observance of ultraorthodox Judaism includes a variety of observances some of which are listed in Table I . 3 , 4 , 5 , 6 , 7 , 8 The following patient case series addresses some of the rare dermatologic manifestations of Ashkenazi ultraorthodox Jewish observance throughout the life cycle. Ashkenazi Jews are those who are of Eastern European descent.…”
Section: Introductionmentioning
confidence: 99%